Effects Of Suckling Versus Weaning On Performance Of Primiparous Gir (Bos Indicus) Cows And On Growth Rate Of Their Calves - Ghodasara, S. N.; Murthy, K. S.; Gajbhiye, P. U.; Savsani, H. H. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Weaning is generally practiced in dairy and beef cattle for achieving better growth rates by giving balance feed in foreign countries. In indigenous dairy cattle it is necessary to evaluate the effect of weaning and suckling on calf growth parameters and reproductive performance of dams. Fifty eight primiparous Gir cows and their calves were taken in to consideration for the study of these two managemental system including disease resistance and its effect on milk yield and lactation length. Significant differences (P
Keywords: Gir cattle; Primiparous; Suckling; Weaning; Disease resistance; calf growth; Reproductive performance